REVITALISASI INDUSTRI KEHUTANAN DALAM PENGELOLAAN HUTAN TANAMAN RAKYAT UNTUK PEMBERDAYAAN KELUARGA PETANI DAN MENDUKUNG INDUSTRI PLYWOOD DI PROVINSI KALIMANTAN TIMUR - Ismail Ismail; Zuhdi Yahya (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The purpose of this research is to study influence accration of growth volume and financial analysis using silvikultur tehnique, in which Albizia,sp. Accration of growth volume used MAI and CAI and financial properness analysis used formula PP, NPV, EAA, Net B/C, and IRR. This research started on November 2009 until January 2010, This research was carried out at PT Belantara Subur, Sote Subdistrict, District of Penajam Paser Utara, East Kalimantan Province started on Macrh 2008 until May 2009.The result of this research shows that the growth of Albizia sp. was influence by silvikultur tehnique and have growth volume about 31,17 m3/Ha/Years, diameters about 38 cm and 61,5 cm, economic cycles in 10 years and feasibility.